Sherlock the Beagle : viral advertising success or public relations disaster? - Robson, Karen; Pitt, Leyland (London : SAGE Publications Ltd, 2017)
KLM, the Dutch national airline, produced a YouTube ad featuring a lovable beagle called Sherlock, who used his acute sense of smell to reunite passengers with the items they left behind on airplanes. The video quickly went viral, achieving millions of downloads. Major news outlets and customers believed the video to be true, only to find out after a few days that while the story was cute, it wasn't true at all. Customer misconceptions spread like wildfire via social media, resulting in consumer backlash. KLMs share price also declined over this period. This case explores the controversy around a seemingly well-intentioned yet grossly misunderstood ad, and encourages students to consider issues related to why the problem occurred and how KLM should respond.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; KLM (Airline); Viral marketing; Consumer behavior